Paraguay : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2006)
This report on the Observance of Standards and Codes on Paraguay examines the Fiscal Transparency Module. Paraguay has made important progress toward greater fiscal transparency. The fairly comprehensive financial administration law has been complemented by legal reforms that eliminated most tax exemptions, revamped revenue administration procedures, and introduced standardized transparency requirements for public procurement, all of which reduce the scope for corruption. The framework for public employment should be modernized to increase the role of merit-based transparent and objective criteria in the hiring, selection, and promotion procedures.